A new species of Microhyla (Anura: Microhylidae) from Sumatra, Indonesia - Vestidhia Y. Atmaja; Amir Hamidy; Tuty Arisuryanti; Masafumi Matsui; Eric N. Smith (Treubia, 2018)
A new species of frog in the genus Microhyla is described from Sumatra, Indonesia based on molecular and morphological characters. This new species was previously confused with M. achatina, a Javan endemic. This new species is diagnosable from its congeners by possessing a medium size (SVL in adult males 18.20–21.32 mm, in adult females 20.37–25.51 mm), a stout body, a nostril–eyelid length being about half of the snout length, having a single outer palmar tubercle, a tibiotarsal articulation reaching the center of the eye (when the hindlimbs are stretched and adpressed to the body), having finger and toe tips dilated, having the dorsum with medial longitudinal grooves, and excibiting a very thin and short dark stripe on the temporal region above a wider cream stripe, extending from the postorbital area to insertion of forelimb. Additionally, the new species is characterized by possessing relatively little foot webbing. Uncorrected 16S rRNA sequence divergences between the new taxon and sequences for other congeneric species available ranged from 4.8 to 15.0%.